Mechanisms of sterilizing immunity provided by an HIV-1 neutralizing antibody against mucosal infection. - Elie Richel; Arne Cordsmeier; Larissa Bauer; Kirsten Fraedrich; Ramona Vestweber; Berit Roshani; Nicole Stolte-Leeb; Armin Ensser; Christiane Stahl-Hennig; Klaus Überla (PLoS Pathogens)
Broadly neutralizing antibodies (bnAbs) against HIV-1 have been shown to protect from systemic infection. When employing a novel challenge virus that uses HIV-1 Env for entry into target cells during the first replication cycle, but then switches to SIV Env usage, we demonstrated that bnAbs also prevented mucosal infection of the first cells. However, it remained unclear whether antibody Fc-effector functions contribute to this sterilizing immunity. Therefore, additional challenge viruses were produced that contain SIV Env and graded doses of a fusion-defective trimer of HIV-1 Env, to which the bnAb, PGT121 can bind without interfering with the SIV Env-based cell entry. After administration of either PGT121 or its mutant deficient in Fc-effector functions, rhesus macaques were intrarectally exposed to these challenge viruses and to those using either HIV-1 Env or SIV Env for entry into the first cells. Both antibodies similarly reduced infection events with the challenge virus using HIV-1 Env by a factor close to 200. Incorporating fusion-defective HIV-1 Env trimers into the particles of the challenge viruses at densities observed in primary virus isolates did not reduce SIV Env-mediated infection events. The results indicate that the sparsity of bnAb binding-sites on HIV-1 virions limits the contribution of Fc-effector functions to provide sterilizing immunity against mucosal viral infection. Hence, harnessing Fc-effector functions for sterilizing immunity against mucosal HIV-1 infection may require strategies to increase the degree of antibody opsonization.